A new in vivo model of pantothenate kinase-associated neurodegeneration reveals a surprising role for transcriptional regulation in pathogenesis - Pandey, Varun; Turm, Hagit; Bekenstein, Uriya; Shifman, Sagiv; Kadener, Sebastian (Frontiers in Cellular Neuroscience, 2013)
Pantothenate Kinase-Associated Neurodegeneration (PKAN) is a neurodegenerative disorder with a poorly understood molecular mechanism. It is caused by mutations in Pantothenate Kinase, the first enzyme in the Coenzyme A (CoA) biosynthetic pathway. Here, we developed a Drosophila model of PKAN (tim-fbl flies) that allows us to continuously monitor the modeled disease in the brain. In tim-fbl flies, downregulation of fumble, the Drosophila PanK homologue in the cells containing a circadian clock results in characteristic features of PKAN such as developmental lethality, hypersensitivity to oxidative stress, and diminished life span. Despite quasi-normal circadian transcriptional rhythms, tim-fbl flies display brain-specific aberrant circadian locomotor rhythms, and a unique transcriptional signature. Comparison with expression data from flies exposed to paraquat demonstrates that, as previously suggested, pathways others than oxidative stress are affected by PANK downregulation. Surprisingly we found a significant decrease in the expression of key components of the photoreceptor recycling pathways, which could lead to retinal degeneration, a hallmark of PKAN. Importantly, these defects are not accompanied by changes in structural components in eye genes suggesting that changes in gene expression in the eye precede and may cause the retinal degeneration. Indeed tim-fbl flies have diminished response to light transitions, and their altered day/night patterns of activity demonstrates defects in light perception. This suggest that retinal lesions are not solely due to oxidative stress and demonstrates a role for the transcriptional response to CoA deficiency underlying the defects observed in dPanK deficient flies. Moreover, in the present study we developed a new fly model that can be applied to other diseases and that allows the assessment of neurodegeneration in the brains of living flies.